ESPECULAÇÃO IMOBILIÁRIA E A PRODUÇÃO DE CONDOMÍNIOS FECHADOS NA AMÉRICA LATINA: O CASO DA REGIÃO DE COLINAS DEL URUBO NA CIDADE DE SANTA CRUZ DE LA SIERRA - BOLÍVIA - Limachi, Ivan Ulises Surco (2021)
This work aims to analyze the increase in closed condominiums in the Urubo region of the city of Santa Cruz de la Sierra - Bolivia - based on the understanding of the role of urban space producing agents, with an emphasis on the market and real estate speculation and in view of the resulting socio-spatial segregation process. This is done through the socioeconomic characterization of the Urubo region, related to land use and the evolution of urban occupation of the area taken as a case study. The construction of the contemporary Latin American city has generated new urban configurations and different types of closed condominiums for housing use, almost always financed by the middle and upper classes in the countries in this context. Closed condominiums are the object of study, understood in this dissertation as residential developments strongly driven by real estate sectors aimed at the maximum use of land value, aiming at their subsequent speculation. The dissertation also seeks, as a complementary objective, to identify the impacts of the so-called closed urbanization - resulting from the condominium logic of living in the region under study - and to relate them in urban terms regarding the scope of the quality of urban life, or even, the level of urbanity of the region. The research will be developed through exploratory, descriptive and explanatory methodologies, with qualitative bases and applied to the object of study of the dissertation.